The Multi‑Occasion Collection Design for Digital Natives Based on Postmodernism - Akkharanet, Papawarin; Ponglawhapun, Atthaphon (วารสารดีไซน์เอคโค, 2026)
Digital Natives—particularly those in Generation Z—have grown up immersed in digital technology, leading to multitasking lifestyles that blur the boundaries between work, socialising and leisure. Yet both the fashion industry and design research have largely overlooked their need for garments that transition seamlessly across these contexts. This mixed‑methods study seeks to fill that gap by identifying digital natives’ apparel preferences, analysing their dressing styles, integrating postmodern art concepts into fashion design, and developing and evaluating a multi‑occasion collection. We conducted a four‑step process combining a quantitative survey with 40 participants, qualitative style analysis using a paper‑doll dataset, documentary analysis of postmodern artworks, and research‑through‑design practice. The findings show that Generation Z respondents favour versatile pieces with loose silhouettes, monochromatic and neutral palettes dominated by black, and materials with smooth textures and subtle patterns. Postmodern art analysis revealed themes of minimalism, appropriation, deconstruction and mixed‑media assemblage, which informed a five‑look collection— “Synsation: Synthetic Sensation”— that uses mixed‑media knitting and modular elements to enable reconfiguration for multiple occasions. By integrating consumer data, art theory and creative practice, this research demonstrates how fashion design can serve as a rigorous mode of inquiry and offers a transferable framework for future multi‑occasion apparel development.